2015
DOI: 10.1007/s00300-015-1853-2
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbon storage, respiration potential, and organic matter quality across an age and climate gradient in southwestern Greenland

Abstract: Geological factors influence biological cycling of organic carbon in soils but are not well represented in our understanding of Arctic carbon dynamics. Landscape age, for instance, directly affects quantity and quality of soil carbon, which are two strong controls of the temperature sensitivity of soil organic matter. We investigated soil carbon storage, respiration potential, and organic matter quality for microbial decomposition across a climate and landscape age gradient in southwest Greenland that deglacia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
(34 reference statements)
1
10
0
Order By: Relevance
“…We expected that differences in vegetation height were correlated with differences in abiotic characteristics, but the environmental variables we measured were remarkably similar between study areas. Both sampling areas were deglaciated approximately 7000 ka (Levy et al 2012), and landscape age has been shown to have a significant effect on soil characteristics, such as C storage (Bradley-Cook and Virginia 2015). Adiabatic winds from the GrIS, which we did not measure, could be one cause for the observed differences in plant height if the winds increase evapotranspiration in an already arid environment or cause damage to plant tissues (Larcher 2003).…”
Section: Homogeneity Of the Study Areasmentioning
confidence: 99%
“…We expected that differences in vegetation height were correlated with differences in abiotic characteristics, but the environmental variables we measured were remarkably similar between study areas. Both sampling areas were deglaciated approximately 7000 ka (Levy et al 2012), and landscape age has been shown to have a significant effect on soil characteristics, such as C storage (Bradley-Cook and Virginia 2015). Adiabatic winds from the GrIS, which we did not measure, could be one cause for the observed differences in plant height if the winds increase evapotranspiration in an already arid environment or cause damage to plant tissues (Larcher 2003).…”
Section: Homogeneity Of the Study Areasmentioning
confidence: 99%
“…After the incubation period, we collected a 10-mL gas sample from the jar headspace, on which we measured CO 2 concentration by injecting the gas into a LiCor-8100 infrared gas analyzer via a trace gas extension valve (LiCor products, Lincoln, NE). We measured the headspace volume for each sample using a dilution function [78] as described in Bradley-Cook and Virginia [79] in order to calculate CO 2 production from headspace concentration.…”
Section: Laboratory Incubation Experimentsmentioning
confidence: 99%
“…Since the last deglaciation, predominantly periglacial processes reshaped the glacial landscape ( Stäblein , ; Ozols and Broll , ; Willemse et al., ; Henriksen , ; Müller et al., ). The maximal possible time for soil formation since the last deglaciation is around 10,000 years in SISI and 6,800 years in RUSS ( cf Bradley‐Cook and Virginia , ). Dominant soils are acid haplic Cambisols and Cryosols in both study areas ( Stäblein , ; Jones et al., ; Henkner et al., ; Kühn and Henkner , ).…”
Section: Methodsmentioning
confidence: 99%
“…However, the estimation of soil organic carbon stocks (SOCS) of permafrost‐affected soils is highly uncertain as, for one reason, there is an unbalanced distribution of studies across the Arctic focusing on Alaska, Siberia and Canada, while Greenland is underrepresented ( Tarnocai et al., ; Hugelius et al., ; Köchy et al., ; Ping et al., ). For West Greenland predominantly Umbrisols and Cambisols are reported ( cf Jensen et al., ; Bradley‐Cook and Virginia , ; Petrenko et al., ; Kühn and Henkner , ), which could store a significantly higher amount of SOC than thin and less developed soils in East and North Greenland ( Elberling et al., , ; Palmtag et al., , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation